The Impact of Parental Divorce on Adolescent Social Behavior: An Islamic Legal Perspective - Dwi Afifah, Adila; Elvionita, Elsa; Yusrial, Yusrial; Ringgit, Awang (Samara: Journal of Islamic Law and Family Studies, 2024)
Adolescents, as individuals in the transitional phase toward adulthood, are highly vulnerable to changes in the family environment, especially those resulting from parental divorce. This study is motivated by concerns over the increasing incidence of social dysfunction among adolescents from divorced families, such as declining academic performance, deviant behavior, and emotional disturbances. The study aims to analyze and describe in depth the impact of parental divorce on adolescents' social behavior, both from psychological and social perspectives, and to examine the issue through the lens of Islamic law. Additionally, this study aims to identify efforts that can be made to ensure that adolescents maintain good social and moral resilience after their parents' divorce. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The study was conducted on several adolescents from divorced families. Data analysis was performed through data reduction, data presentation, and inductive conclusion-drawing. The results of the study indicate that parental divorce has a significant impact on adolescents' social behavior. The implications of this study are the need for active roles from various parties, such as extended families, communities, schools, and religious institutions, to provide emotional and spiritual support to adolescents who are victims of divorce. Additionally, there is a need for regulations that strengthen parents' obligations in raising children post-divorce to ensure their healthy social and spiritual development. This study is expected to serve as an academic and practical reference in developing an inclusive social support system for adolescents affected by divorce.